2020
DOI: 10.4143/crt.2019.703
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia+ Chronic Myeloid Leukemia with CALR Mutation: A Case Report and Literature Review

Abstract: Myeloproliferative neoplasms (MPNs) are classified as chronic myeloid leukemia (CML) and Philadelphia chromosome-negative MPN. In MPN cases, the presence of a <i>BCR-ABL1</i> translocation with a coexisting mutation is exceptionally rare. Herein, we report the first documented patient with CML harboring <i>CALR</i> mutation in Korea. A 33-year-old woman was referred to our hospital in February 2015 with splenomegaly, leukocytosis, and thrombocytosis. She was diagnosed with CML and start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…However, regardless of the BCR::ABL1 level, the mutant CALR allele burden remained stable from diagnosis to follow-up visit. Similar to the patient in this case, Yoon et al 23 reported that the major MR was reached after using nilotinib, but the PLT count remained high. After switching to dasatinib, the thrombocytosis got worse and CALR mutations were discovered in primary material.…”
supporting
confidence: 83%
“…However, regardless of the BCR::ABL1 level, the mutant CALR allele burden remained stable from diagnosis to follow-up visit. Similar to the patient in this case, Yoon et al 23 reported that the major MR was reached after using nilotinib, but the PLT count remained high. After switching to dasatinib, the thrombocytosis got worse and CALR mutations were discovered in primary material.…”
supporting
confidence: 83%
“…Including our case, a total of 24 cases with concomitant BCR::ABL1 and CALR mutation have been described so far ( Bonzheim et al, 2015 ; Cabagnols et al, 2015 ; Loghavi et al, 2015 ; Diamond et al, 2016 ; Seghatoleslami et al, 2016 ; Dogliotti et al, 2017 ; Gilles et al, 2017 ; Kandarpa et al, 2017 ; Blouet et al, 2018 ; Boddu et al, 2018 ; De Roeck et al, 2018 ; Klairmont et al, 2018 ; Lewandowski et al, 2018 ; Xia et al, 2019 ; Balducci et al, 2020 ; Da Costa et al, 2020 ; Guidotti et al, 2020 ; Liu et al, 2020 ; Yoon et al, 2020 ; Sobieralski et al, 2022 ; Huo et al, 2023 ).…”
Section: Results Of Literature Cases and The Present Casementioning
confidence: 96%
“…The association of CALR mutations with BCR::ABL1 rearrangement is much rarer, being reported in isolated cases. In this article, we described a case from our daily practice with a long history of CALR -mutated PMF, subsequently developing CML with gaining of BCR::ABL1 rearrangement; meanwhile, through a literature search, we identified 23 cases harboring both CALR mutation and BCR::ABL1 rearrangement ( Bonzheim et al, 2015 ; Cabagnols et al, 2015 ; Loghavi et al, 2015 ; Diamond et al, 2016 ; Seghatoleslami et al, 2016 ; Dogliotti et al, 2017 ; Gilles et al, 2017 ; Kandarpa et al, 2017 ; Blouet et al, 2018 ; Boddu et al, 2018 ; De Roeck et al, 2018 ; Klairmont et al, 2018 ; Lewandowski et al, 2018 ; Xia et al, 2019 ; Balducci et al, 2020 ; Da Costa et al, 2020 ; Guidotti et al, 2020 ; Liu et al, 2020 ; Yoon et al, 2020 ; Sobieralski et al, 2022 ; Huo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in case of persistent thrombocytosis without leukocytosis and negative driver mutations, BCR::ABL1 will be researched to avoid missing atypical presentation of CML. Although, classical driver mutations are mutually exclusive, rare cases of CML with JAK2 or CALR mutations have been observed [ 44 , 102 , 103 ]. The temporal sequence of these mutations is variable suggesting that the alterations might reside in the same or distinct clones [ 40 , 42 , 43 ].…”
Section: Bcr::abl1 -Positive Mpn: Chronic Myeloid Leukemia (...mentioning
confidence: 99%